On the nature and causes of poverty: an analysis of some aspects of Adam Smith’s social philosophy - Sérgio de Toledo Fonseca, Fernando; Höher, Ricardo (Revista Economia Ensaios, 2024)
Adam Smith's idea of poverty has been misinterpreted in some literature for associating pauperism with his vision of liberal laissez-faire. There are few works that discuss Smith's idea about the causes of poverty. This article exposes some aspects of the economist's social philosophy, based on a theoretical review of his main works and works by researchers of Smithian thought. The work concludes that Smith offers ethical arguments in favor of the free market to improve the living conditions of the poor, recognizing the economic and motivational aspects of the complex phenomenon of poverty.